Development and validation of a novel prognostic score to predict survival in patients with metastatic colorectal cancer: the metastatic colorectal cancer score (mCCS). (18th March 2019) - Marschner, N.; Frank, M.; Vach, W.; Ladda, E.; Karcher, A.; Winter, S.; Jänicke, M.; Trarbach, T.
Abstract: Aim: Published prognostic scores for metastatic colorectal cancer (mCRC) are based on data from highly selected patient subgroups with specified first‐line treatments and may not be applicable to routine practice. We have therefore developed and validated the metastatic colorectal cancer score (mCCS) to predict overall survival (OS) for patients with mCRC. Method: A total of 1704 patients from the prospective, multicentre cohort study Tumour Registry Colorectal Cancer were separated into learning ( n  = 796) and validation ( n  = 908) samples. Using a multivariate Cox regression model, the six‐factor mCCS was established. Results: The six independent prognostic factors for survival are as follows: two or more metastatic sites at the start of first‐line treatment, tumour grading ≥ G3 at primary diagnosis, residual tumour classification ≥ R1/unknown, lymph node ratio (of primary tumour) ≥ 0.4, tumour stage ≥ III/unknown at primary diagnosis and KRAS status mutated/unknown. The mCCS clearly separated the learning sample into three risk groups: zero to two factors (low risk), three factors (intermediate risk) and four to six factors (high risk). The prognostic performance of the mCCS was confirmed in the validation sample and additionally stratified a large sample of patients with known ( K)RAS mutation status. Conclusion: The novel prognostic score, mCCS, clearly defines three prognostic groups for OS at start of first‐line therapy. For oncologists, the mCCS represents a simple and easy‐to‐apply tool for routine clinical use, as it is based on objective tumour characteristics and can assist with treatment decision‐making and communication of the prognosis to patients.